Analisis Hukum Internasional Terhadap Keterlibatan Sindikat Internasional serta Lemahnya Pengawasan Perbatasan : Studi Kasus Tindak Pidana Perdagangan Orang di Batam Tahun 2022 - 2023 - Pamungkas, Imam Chandra; Sutrisno, Andri (PT Elaborium Elevasi Indonesia, 2025)
Batam is one of Indonesia's strategic border areas that is highly vulnerable to human trafficking. Its geographical position, which is close to Singapore and Malaysia, along with high labor mobility, makes Batam a primary transit point for international syndicates engaged in human trafficking. This study analyzes the involvement of international syndicates in human trafficking cases in Batam during 2022–2023 and examines the weaknesses of border surveillance from the perspective of international law. The research employs a normative juridical approach, analyzing international legal frameworks, national regulations, and case studies of human trafficking in Batam. The findings reveal that weak border surveillance in Batam facilitates international syndicates in recruiting, smuggling, and exploiting victims, particularly women and children. Although Indonesia has ratified various international legal instruments such as the Palermo Protocol and the United Nations Convention Against Transnational Organized Crime, the enforcement and coordination among law enforcement agencies remain suboptimal. This study recommends strengthening border surveillance through technological advancements, enhancing international cooperation, and harmonizing national regulations with international legal standards to reduce human trafficking cases in Batam.